PEMPHIGOID GESTATIONIS - Kelly, S; Wojnarowska, F (1994)
Pemphigoid gestationis is a rare autoimmune bullous dermatosis of pregnancy and the postnatal period. It shares clinical and immunological features with bullous pemphigoid and is best regarded as a member of the pemphigoid group of blistering conditions. It most commonly affects multiparous women in the second or third trimester. Diagnosis is made by the demonstration of immunoreagents in the epidermal basement membrane and the presence of a circulating complement fixing anti basement membrane antibody. The disease may be controlled by the administration of corticosteroids and may be expected to resolve in the months following delivery. Prolonged disease may occur. Relapse in subsequent pregnancies is common. The condition is thought to be triggered by a local allogeneic response in the placenta in genetically susceptible women.